The effect of fasting in Ramadan on patients with heart disease - Awad, Abdul ameer J. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Knowledge about the clinical problems during the fast of Ramadan is important in order to opens the way to further research aimed at discovering the significance of Ramadan fasting in patients with heart disease. Patients and Methods: Eighty-six outpatients with heart disease with intention to fast were studied in the month of Ramadan 2010 (1430 H) at the Ibn Al-bitar Hospital. Detailed clinical and biochemical assessments were performed within 3 days before the start of Ramadan and then on the last day of Ramadan. Results: There were 54 (62.8%) males and 32 (37.2%) females with a mean age of 56.3 years (range, 17-84 ). Forty-six patients (53%) had coronary artery disease, 23 patients (27%) had valvular heart disease, 13 patients (15%) had congestive heart failure and 4 patients (5%) were treated for arrhythmia. Sixty-two patients (72%) were in New York Heart Association (NYHA) Class I, 18 patients (21%) in Class II, and 6 patients (7%) were in Class III. Seventy-four patients (86%) managed to fast during the entire Ramadan, 9 patients (10.4%) missed the fasting for up to 7 days, and 3 patients (3.5%) could not fast. There were no significant changes in the NYHA Class (p=0.12). No significant changes occurred in any of the hematological or biochemical parameters during the fasting of Ramadan. Conclusion: The effects of fasting during Ramadan on stable patients with cardiac disease are minimal. The majority of patients with stable cardiac disease can fast during Ramadan without significant detrimental effects.